2016
DOI: 10.1016/j.jgeb.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphism in ovine Calpain gene and growth performance in three Egyptian sheep breeds

Abstract: The aim of the present study was to assess the association of single nucleotide polymorphisms (SNPs) of Calpain (CAPN) gene with birth weight (BW), final weight (FW) and average daily gain (ADG) in three Egyptian sheep breeds: Barki, Rahmani and Ossimi. Blood samples were collected from 108 animals representing the three breeds. DNA was isolated using salting out procedure and then the quality and quantity of DNA extracted were measured. A 190 bp of CAPN was amplified by PCR using specific primers. The allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Calpain substrates consist of a variety of enzymes such as cytoskeletal proteins (Fedota et al, 2016) and epidermal growth factor receptors (Glading et al, 2000). The CAPN gene was investigated as a potential candidate gene for growth trait as reported in earlier studies of Mahrous et al, 2016;Hou et al, 2011;and Bosques et al, 2015. Amplification of CAPN1 gene in 5'UTR fragment was successfully conducted using PCR for all samples.…”
Section: Discussionmentioning
confidence: 99%
“…Calpain substrates consist of a variety of enzymes such as cytoskeletal proteins (Fedota et al, 2016) and epidermal growth factor receptors (Glading et al, 2000). The CAPN gene was investigated as a potential candidate gene for growth trait as reported in earlier studies of Mahrous et al, 2016;Hou et al, 2011;and Bosques et al, 2015. Amplification of CAPN1 gene in 5'UTR fragment was successfully conducted using PCR for all samples.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LIM Homeobox 3 (LHX3) and LIM Homeobox 4 (LHX4) serve as a transcription factors for sheep body growth and reproduction process [11,12]. A PCR study has identified genetic variants in ovine Calpain (CAPN) gene which are related with meat tenderness and growth performance traits in sheep [13][14][15]. Calpains (CAPN) encodes intracellular calcium-activated cysteine proteases that work in physiological and pathological processes.…”
Section: Genes Associated With Growth and Body Weightmentioning
confidence: 99%
“…Egyptian breeds are fat-tailed that characterized by extended breeding seasons, high fertility, and well adapted to harsh environmental conditions (Galal et al, 2005;EL-Hanafy and El-Saadani, 2009Mahrous et al, 2016, Barakat et al, 2017El-Malky et al, 2019).The total number of Egyptian sheep breeds is raised from 5,463,169 head in 2015 to 5,697,716 head in 2017. Sheep provide 72,296 tons of meat, they contribute 6% of the total red meat produced in Egypt and 99,322 tons of fresh milk (FAO, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is a very useful technique in early prediction and comparing animals with different economically important characteristics like growth traits (Dunn and Ryan, 2015). The growth hormone (GH), insulin-like growth factor-1 (IGF-1) and leptin genes are candidates for growth in ovine since they play a key role in growth regulation and development (Barzehkar et al 2009, Nazari et al, 2016Mahrous et al, 2016).…”
Section: Introductionmentioning
confidence: 99%